2021
DOI: 10.14218/jcth.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

Significant Histologic Changes Are Not Rare in Treatment-naive Hepatitis B Patients with Normal Alanine Aminotransferase Level: A Meta-analysis

Abstract: Background and Aims Chronic hepatitis B is the main cause of liver cancer. However, the most neglected group has been treatment-naive chronic hepatitis B patients with normal alanine aminotransferase (ALT). People have tended to subjectively assume that the liver lesions of these patients are not serious and do not need antiviral treatment. However, the truth is not as optimistic as we thought. We aimed in this study to analyze the proportion of significant inflammation or fibrosis in aforemention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…13 Furthermore, significant proportion of those with persistently normal serum ALT shared significant inflammation (35%), significant fibrosis (30%), and cirrhosis (3%) in a recent meta-analysis. 14 Especially, the rates of significant inflammation, significant fibrosis, and cirrhosis were not different between the HBeAg positive and HBeAg negative patients. Older age over 40 years was significantly associated with fibrosis and liver cirrhosis.…”
Section: Unmet Needs In Application Of Guidelines To the Real-life Pr...mentioning
confidence: 87%
See 3 more Smart Citations
“…13 Furthermore, significant proportion of those with persistently normal serum ALT shared significant inflammation (35%), significant fibrosis (30%), and cirrhosis (3%) in a recent meta-analysis. 14 Especially, the rates of significant inflammation, significant fibrosis, and cirrhosis were not different between the HBeAg positive and HBeAg negative patients. Older age over 40 years was significantly associated with fibrosis and liver cirrhosis.…”
Section: Unmet Needs In Application Of Guidelines To the Real-life Pr...mentioning
confidence: 87%
“…reported that those who are clinically considered to be in the immune‐tolerant phase (HBeAg positive, HBV DNA > 20 000 IU/mL, serum ALT < 19 U/L for female and < 30 U/L for male) had significantly higher risks of HCC (hazard ratio [HR] 2.54, 95% confidence interval [CI] 1.54–4.18) and death/transplantation (HR 3.38, 95% CI 1.85–6.16) than those of NA‐treated immune‐active phase patients 13 . Furthermore, significant proportion of those with persistently normal serum ALT shared significant inflammation (35%), significant fibrosis (30%), and cirrhosis (3%) in a recent meta‐analysis 14 . Especially, the rates of significant inflammation, significant fibrosis, and cirrhosis were not different between the HBeAg positive and HBeAg negative patients.…”
Section: For Those Within Immune‐tolerant Phasementioning
confidence: 99%
See 2 more Smart Citations
“…However, the proportion of moderate to severe inflammation in CHB patients with normal ALT was inconsistent in different studies, and most of them are small sample studies. Subsequently, we performed a meta‐analysis that included 2771 individuals (19 studies) 7 . Our results showed a high rate of moderate to severe inflammation and significant fibrosis confirmed by liver biopsy in up to 35% (95% confidence interval [CI] 27%–43%) and 30% (95% CI 25%–36%).…”
Section: Introductionmentioning
confidence: 91%